Sperm motility initiating substance may be insufficient to induce forward motility of Cynops ensicauda sperm. Issue 8 (6th July 2017) - Sato, Tae; Yokoe, Misato; Endo, Daisuke; Morita, Masaya; Toyama, Fubito; Kawamura, Yuuki; Nakauchi, Yuni; Takayama‐Watanabe, Eriko; Watanabe, Akihiko
Abstract : Sperm motility‐initiating substance (SMIS) is a key protein for internal fertilization of the newt, Cynops pyrrhogaster, and commonly enhances forward sperm motility in some amphibian species, including external fertilizers. SMIS action varies among different species in correlation with a species‐specific reproductive environment. In the present study, we identified the gene of C. ensicauda SMIS ( Ce SMIS) and examined the mechanism of SMIS action with reference to that of the closely related Cynops species. The Ce SMIS was identified by a 176‐amino acid sequence including seven amino acids critical for the initiation of sperm motility. The amino acid sequence showed 91% homology to the whole sequence of C. pyrrhogaster SMIS ( Cp SMIS). By immunostaining with an anti‐ Cp SMIS antibody, Ce SMIS was shown to be localized in the outer layer of the egg jelly. A peptide presenting the active site of SMIS was observed to bind to the axial rod of the midpiece in C. ensicauda sperm. The localization and binding patterns of Ce SMIS were fundamentally similar to those of Cp SMIS. However, the SMIS peptide did not induce forward motility of C. ensicauda sperm, although it induced a fast wave of the undulating membrane. Forward sperm motility was induced in the egg jelly extract containing Ce SMIS. These results suggest that the mechanism of initiation of sperm motility is differentiated between C. ensicauda and C. pyrrhogaster .